What About the Actor's Formant in Actresses' Voices? - Master, Suely [UNESP]; De Biase, Noemi Grigolleto; Madureira, Sandra (Mosby-elsevier, 2012)
Spectrographic analysis of male actors' voices showed a cluster, the actor's formant (AF), which is related to the perception of good and projected voice quality. To date, similar phenomena have not been described in the voices of actresses. Therefore, the objective of the current investigation was to compare actresses' and nonactresses' voices through acoustic analysis to verify the existence of the AF cluster or the strategies used to produce the performing voice. Thirty actresses and 30 nonactresses volunteered as subjects in the present study. All subjects read a 40-second text at both habitual and loud levels. Praat (v.5.1) was then used to analyze equivalent sound pressure level (Leq), speaking fundamental frequency (SFF), and in the long-term average spectrum window, the difference between the amplitude level of the fundamental frequency and first formant (L1 - L0), the spectral tilt (alpha ratio), and the amplitude and frequency of the AF region. Significant differences between the groups, in both levels, were observed for SFF and L1 - L0, with actresses presenting lower values. There were no significant differences between groups for Leq or alpha ratio at either level. There was no evidence of an AF cluster in the actresses' voices. Voice projection for this group of actresses seemed to be mainly a result of a laryngeal setting instead of vocal tract resonances.
Keywords: Speech acoustics; Long-term average spectrum; Voice quality; Voice training; Performing voice; Vocal projection